2014
DOI: 10.1111/1756-185x.12287
|View full text |Cite
|
Sign up to set email alerts
|

Alkaptonuric ochronosis: a clinical study from Ardabil, Iran

Abstract: Alkaptonuria is a rare autosomal recessive disorder of the metabolism caused by deficiency of homogentisic acid oxidase. It is suggested that more widespread screening should be undertaken in order to assess the true incidence of the disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 19 publications
(36 reference statements)
1
4
0
2
Order By: Relevance
“…The chief complaint of our patient was acute knee pain, which is observed in 5 out of 7 patients, as reported by Azami et al in Ardabil, but not as the chief complaint [12]. Knee pain has been reported as an accidental finding during a physical examination or imaging survey [13].…”
Section: Discussionsupporting
confidence: 67%
“…The chief complaint of our patient was acute knee pain, which is observed in 5 out of 7 patients, as reported by Azami et al in Ardabil, but not as the chief complaint [12]. Knee pain has been reported as an accidental finding during a physical examination or imaging survey [13].…”
Section: Discussionsupporting
confidence: 67%
“…In addition, manifestation of alkaptonuria in cluster among the family members is reported (7). Azami et al reported that the mean age of patients with ochronotic arthropathy was 46.1 years and recommended more perfect screening to assess the true incidence of this disorder (10). Considering previous reports, the age of diagnosis of the current case was interestingly late which was correlated with the lack of appropriate healthcare facilities in the corresponding rural region.…”
Section: Discussionmentioning
confidence: 89%
“…Bu nedenle alkaptonüri aynı zamanda siyah idrar hastalığı olarak da adlandırılmaktadır. 5 Ancak yeni alınmış idrar görünümü normal olup, alkalize olunca veya oksitlenince koyulaşır. 11 Alkaptonüri tanısı, idrar veya kanda gazlikid kromatografisi ile kantitatif HGA düzeyi spesifik olarak saptanarak konulabilir.…”
Section: Discussionunclassified
“…Alkaptonürinin henüz etkinliği kanıtlanmış bir tedavisi yoktur. 5,10 Erken evrelerinde semtomatik tedavi yeterli olabilmektedir, ancak dejenerasyonun geliştiği son evrelerinde total eklem ve kalp kapak replasmanı gerekebilmektedir. 15 Hastalığın erken dönemlerinde, tedavide öncelikli olarak artropati, kardiyak ve üriner sistem tutulum ve komplikasyon açısından yakın izlem önemlidir.…”
Section: Resi̇munclassified